Analisis Nilai Tambah dan Kelayakan Usaha Pengolahan Ikan Asin (Studi kasus: Desa Percut, Kec. Percut Sei Tuan, Kab. Deli Serdang) - Sartika Sartika; Mitra Musika Lubis; Khairul Saleh (Universitas Medan Area, 2022)
The purpose of this study was to determine the value added and the feasibility of processing fish into salted fish. This research was conducted in Percut Village, Percut Sei Tuan Subdistrict which is located in a coastal area which has quite good fishery potential and the average villager has a livelihood as a fisherman and most of the housewives of fishing families work as fish processors into salted fish. The sample in this study consisted of 36 respondents. Data analysis was carried out descriptively with added value and feasibility analysis. The results showed that the amount of added value obtained from the processing of salted fish in the research area with raw materials of 67.86 kg of wet fish was obtained as much as 47.14 kg of salted fish every month with a selling price of Rp. 23,000.00/kg and the profit earned is Rp. 421,626.25. The average added value of salted fish processing is Rp. 10,837.22/kg with a ratio of added value of 68.29% 50%, meaning that the added value is quite high. The feasibility analysis revealed that the R/C ratio was greater than 1, namely the processing of salted fish of 1.64. Because the R/C ratio is greater than one, it can be concluded that the salted fish processing business in the research area is feasible.